O stalking e cyberstalking no âmbito familiar e o sistema de proteção às mulheres - Costa Junior, Expedito (2022)
It is proposed in the present dissertation, linked to the line of research of Criminal system and violence, of the PPGCrim of PUCRS, to research the changes in the criminal sphere imposed from the legislative alteration with the new crime of persecution created by the law n.º 14.132, of March 31, 2021 which added art. 147-A to Decree-Law No. 2,848, of December 7, 1940 (Criminal Code), to provide for the crime of stalking and repeal art. 65 of Decree-Law No. 3,688, of October 3, 1941 (Criminal Misdemeanors Law). The objective was to explore the crime of stalking and cyber stalking in the domestic sphere and its integration into the women's protection system, from which a thorough analysis was initially made under the concept, history and types of stalking, as well as the victimology and types of victims persecuted, to the typification of the crime of persecution in our legislation. Then, the main aspects of the new stalking crime, cybercrime, digital evidence and the digital chain of custody were addressed, since such knowledge is fundamental for stalking crimes within the family committed by digital means (cyberstalking). Finally, the Maria da Penha Law and domestic stalking, domestic violence during the pandemic, emergency protective measures and the integration of stalking in the domestic sphere into the women's protection system were discussed. One of the great contributions of the new crime of persecution in situations of domestic violence to the system of protection for women is the fact that this protection network is extended to allow, among other measures, the granting of an urgent protective measure, without the need to that the woman proves a threat or violence, with only one disturbance to her sphere of freedom or privacy being sufficient.